Physiological Responses to Nutrient Accumulation in Trees Seedlings Irrigated with Municipal Effluent in Indian Desert. (23rd July 2014) - Singh, G.; Bhati, Madhulika; Rathod, T. R.; Tomar, U. K.
Abstract : Leaf water potential (Ψ l ), net photosynthesis rate (P N ), transpiration rate (E ), stomatal conductance (g S ), and water use efficiency (WUE) are greatly influenced by the nutrient composition of water which is used for irrigating trees. The above-mentioned physiological variables and foliage mineral concentrations were observed for Eucalyptus camaldulensis, Acacia nilotica, and Dalbergia sissoo plants irrigated with municipal effluent (ME) at 1/2 PET (potential evapotranspiration; T1 ), 1 PET (T2 ), and 2 PET (T3 ) rates and the control plants irrigated with canal water at 1PET (T4 ). Increased mineral concentrations in order T1 < T2 < T3 enhancedΨ l, P N, E, andg S . Relatively greater increase inE thanP N reduced WUE. Available nutrient in ME enhanced physiological function in T2, whereas reduced quantity of water lowered it in T1 than in T4 plants. Differential minerals uptake increased concentrations of N and P in D. sissoo, Mn in E. camaldulensis, and the rest in A. nilotica .P N was more sensitive to environment thanE . Enhanced mineral concentration through ME was beneficial but its differential uptake and accumulation influenced physiological functions and WUE. E. camaldulensis is better for high and continuous loading of effluent and A. nilotica is best for high nutrient uptake. D. sissoo is efficient water user.